2007
DOI: 10.4269/ajtmh.2007.76.875
|View full text |Cite
|
Sign up to set email alerts
|

High Spatial Resolution Mapping of Malaria Transmission Risk in the Gambia, West Africa, Using Landsat Tm Satellite Imagery

Abstract: Understanding local variability in malaria transmission risk is critically important when designing intervention or vaccine trials. Using a combination of field data, satellite image analysis, and GIS modeling, we developed a high-resolution map of malaria entomological inoculation rates (EIR) in The Gambia, West Africa. The analyses are based on the variation in exposure to malaria parasites experienced in 48 villages in 1996 and 21 villages in 1997. The entomological inoculation rate (EIR) varied from 0 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 42 publications
4
83
0
1
Order By: Relevance
“…16 Gambissara is a large village in the upper river region (URR) of the Gambia where malaria transmission is moderate and seasonal (July-December). 17,18 Suspected malaria patients were explained the study objectives and procedures before being asked to sign an informed consent form. For patients < 18 years old, parents/ guardian were asked to sign the informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…16 Gambissara is a large village in the upper river region (URR) of the Gambia where malaria transmission is moderate and seasonal (July-December). 17,18 Suspected malaria patients were explained the study objectives and procedures before being asked to sign an informed consent form. For patients < 18 years old, parents/ guardian were asked to sign the informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Our results agreed with previous findings that proximity to mosquito aquatic habitat is a risk factor for malaria. 3,[29][30][31][32] Proximity to Anopheles production sites has been previously associated with increased adult mosquito density and malaria prevalence. 33,34 The heterogeneous distribution of larval habitats produces large variations in vector-host contact over relatively short distances, 30 whereas the abundance of the biting mosquito population away from those breeding sites reflects dispersal and survival of mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…fly no more than 2 km, a small proportion may fly much further. 23 This longdistance flight may be a consequence of the local ecology of the study area, which is flat, where persons live in small and discrete communities and where breeding sites are often far from the villages. Thus, vectors flying from the abundant breeding sites in the floodplain find it difficult to locate a human blood meal, particularly because those persons living closer to the floodplains are more likely to sleep under bed nets.…”
Section: 21mentioning
confidence: 99%
“…30 Second, not all water bodies in the alluvial floodplains were treated with larvicide because deep water, especially during times of high tides, made it impossible to reach some parts of the wetlands close to the river. Based on earlier published work, 31 we assumed that this might not affect the intervention because these sites were more than 4 km from the study villages and we expected most adult mosquitoes to emerge from the landward edge of the floodplain. Nevertheless, more recent work has shown that low densities of larvae can be found over the entire floodplain area, even close to the river.…”
Section: 21mentioning
confidence: 99%